1984
DOI: 10.1113/jphysiol.1984.sp015139
|View full text |Cite
|
Sign up to set email alerts
|

Responses of upper airway, intercostal and diaphragm muscle activity to stimulation of oesophageal afferents in dogs.

Abstract: SUMMARY1. The effects of oesophageal distension on respiratory patterns and the moving average electromyogram (e.m.g.) activity of three upper airway muscles -the alae nasi, the genioglossus, and the posterior cricoarytenoid -and four chest wall muscles -the costal and crural diaphragm and the inspiratory and expiratory intercostals -were examined in ten anaesthetized, tracheostomized, spontaneously breathing dogs. Distension was produced by inflations of a balloon placed in the middle part of the thoracic oes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…Although the majority of studies on TLESR have been conducted in humans, the phenomenon has been recorded in dogs (6,11,18), cats, and ferrets (3). The LES relaxation is the major criterion for identification of TLESR in the human as well as animal studies (10).…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of studies on TLESR have been conducted in humans, the phenomenon has been recorded in dogs (6,11,18), cats, and ferrets (3). The LES relaxation is the major criterion for identification of TLESR in the human as well as animal studies (10).…”
Section: Discussionmentioning
confidence: 99%
“…Tan & Miller (1986) (1986). Cherniack et al (1984) distended the mid-thoracic oesophagus of the dog using a 10 cm balloon and volumes of 50-200 ml of air. They found a graded inhibition of both costal and crural diaphragm EMG activities, a raised respiratory rate and increased activities of both internal and external intercostals.…”
Section: Discussionmentioning
confidence: 99%
“…Also the electrical activities of alae nasi, genioglossus and PCA were all increased by oesophageal distension. Cherniack et al (1984) speculated that activation of upper airway muscles would allow an intact animal (non-tracheostomized) to lower resistance to airflow and so maintain tidal volume in the face of reduced activity of the major respiratory pump muscles. In contrast, the present study suggests that at least the laryngeal portion of the upper airway does not dilate during oesophageal distension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it has been shown that the re spiratory related activity of the upper-air way dilating muscles and the cranial nerves which supply them are influenced by phasic vagal discharge [7]. With lung inflation, the amount of immediate inhibi tion is larger for all upper-airway dilating muscles than for the diaphragm [8,30].…”
Section: Introductionmentioning
confidence: 99%